R. M. Cid López y M. González González (eds.), Mitos femeninos de la cultura clásica, Oviedo, KRK Ediciones, 2003. ISBN: 84-96119-42-4 (Minerva. Revista de Filología Clásica, 2019)
Reseña de M. Cid López y M. González González (eds.), Mitos femeninos de la cultura clásica, Oviedo, KRK Ediciones, 2003. ISBN: 84-96119-42-4